2011
DOI: 10.1016/j.cognition.2011.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Eye contact facilitates awareness of faces during interocular suppression

Abstract: Eye contact captures attention and receives prioritized visual processing. Here we asked whether eye contact might be processed outside conscious awareness. Faces with direct and averted gaze were rendered invisible using interocular suppression. In two experiments we found that faces with direct gaze overcame such suppression more rapidly than faces with averted gaze. Control experiments ruled out the influence of low-level stimulus differences and differential response criteria. These results indicate an enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
180
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(216 citation statements)
references
References 31 publications
31
180
4
1
Order By: Relevance
“…However, facial stimuli (Kikuchi et al, 2009;Lyyra, MĂ€kelĂ€, et al, 2014;Ro et al, 2001) and their emotional expressions seem to form an exception, and our results suggest that gaze direction may also be implicitly represented in a manner that can exert a similar bottom-up influence speeding up recovery from change blindness. This is also in line with studies using interocular suppression (Akechi et al, 2014;Chen & Yeh, 2012;Stein et al, 2011) and studies using visual search (Conty et al, 2006;Doi et al, 2009;Senju et al, 2005;Shirama, 2012;Von GrĂŒnau & Anston, 1995). In visual search, however, the search advantage for direct gaze has been contested as being confounded by the attention-grabbing effect of the gaze directions of the distractor faces.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…However, facial stimuli (Kikuchi et al, 2009;Lyyra, MĂ€kelĂ€, et al, 2014;Ro et al, 2001) and their emotional expressions seem to form an exception, and our results suggest that gaze direction may also be implicitly represented in a manner that can exert a similar bottom-up influence speeding up recovery from change blindness. This is also in line with studies using interocular suppression (Akechi et al, 2014;Chen & Yeh, 2012;Stein et al, 2011) and studies using visual search (Conty et al, 2006;Doi et al, 2009;Senju et al, 2005;Shirama, 2012;Von GrĂŒnau & Anston, 1995). In visual search, however, the search advantage for direct gaze has been contested as being confounded by the attention-grabbing effect of the gaze directions of the distractor faces.…”
Section: Discussionsupporting
confidence: 81%
“…Yokoyama et al (2011) already observed a similar direct gaze advantage for change detection using both schematic faces with frontal-views and with rotated head-views, the latter with non-symmetrical direct gaze stimuli in the change blindness paradigm. Similarly, in interocular suppression, the facilitated awareness of direct gaze relative to averted gaze is observed for face stimuli with both frontal/symmetrical (Chen & Yeh, 2012) and rotated/asymmetrical head orientation (Stein et al, 2011). Nevertheless, eye contact perception in laterally rotated head stimuli would not completely correspond to the present findings.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…After all, in other circumstances suppression durations of a visual stimulus are impacted by the properties of that stimulus, including its physical characteristics (9), its configural properties (30,66), its affective connotation (67,68), its lexical familiarity (32), and its social connotation (69). However, in all these instances the features defining the suppressed stimulus are plausibly being registered and remain available for analysis (70), albeit with reduced fidelity or signal strength (34).…”
Section: Discussionmentioning
confidence: 99%
“…One visual search study reported better discrimination of direct than averted gaze looking characters situated in the visual periphery (Palanica & Itier, 2011). Other studies using change detection (e.g., Yokoyama et al, 2011) and interocular suppression (e.g., Stein et al, 2011;Yokoyama et al, 2013) also support the view of a preferential processing of direct gaze in faces presented covertly. However, these studies did not manipulate the eccentricity at which those faces were presented or the direction of the face.…”
Section: Introductionmentioning
confidence: 95%